(untitled) (Eurasian Journal of Philology Science and Education, 2015)
The article is devoted to the research of the problem of chronotope. This category is considered on the material of A. Zhaksylykov’s novel «Singing Stones». On the basis of the analysis of time and space the author reveals the peculiarities of the work’s construction. The great attention is given to comprehension of the writer’s aesthetic views, his concept of the world and the person. Features of A.Zh. Zhaksylykov’s concept about categories of time and space are revealed. The national originality of the concept of the prose of the writer are indicated. The influence of national culture, philosophical and religious views of the twentieth century on A.Zh. Zhaksylykov’s work is marked. The detailed analysis of the existential continuum of the novel is carried out. The basic properties of chronotope of this work are indicated. Features of construction of the individually-author’s picture of the world of the writer are revealed. The detailed analysis of the existential continuum of the novel the distinctive features of which are conventionality, multidimensionality, illusiveness is undertaken. It is underlined, that as the major components of the novel chronotope’s are dreams, myths. The basic properties of chronotope of this work are indicated. Features of construction of the writer’s individually-author’s picture of the world are revealed. In this article the nature of time-space’s category and its influence on the narrative structure of work are investigated. Features of chronotope’s functioning in the novel are revealed. The basic types of timespace which have received reflection in the writer’s work are analyzed. The great attention is given to private chronotopes of heroes of this novel. In the article features of the existential position of the work’s characters are revealed.